Genetic manipulation of the pathway for diacetyl metabolism in Lactococcus lactis. - Swindell, S R (1996)
Diacetyl is an important food flavor compound produced by certain strains of citrate-metabolizing lactic acid bacteria. Citrate is converted to pyruvate, from which diacetyl is produced via intermediate alpha-acetolactate. This paper reports the cloning and analysis of the gene (aldB) encoding alpha-acetolactate decarboxylase from Lactococcus lactis MG1363. Deletion of the MG1363 chromosomal aldB gene was achieved by double crossover homologous recombination. The mutant strain was found to produce diacetyl; alpha-acetolactate decarboxylase activity was eliminated. Overexpression of the cloned ilvBN genes (encoding an alpha-acetolactate synthase) in the aldB deletion strain produced even higher levels of alpha-acetolactate, acetoin, and diacetyl.